Impacts of the COVID‐19 pandemic on vegetable production systems and livelihoods: Smallholder farmer experiences in Burkina Faso. (31st October 2021) - Middendorf, B. Jan; Traoré, Hamidou; Middendorf, Gerad; Jha, Prakash K.; Yonli, Djibril; Palé, Siébou; Prasad, P.V. Vara
Abstract: At the onset of COVID‐19, researchers quickly recognized the need for research on the consequences of the pandemic for agricultural and food systems, both in terms of immediate impacts on access to inputs and labor, disruptions in transportation and markets, and the longer‐term implications on crop productivity, income, and livelihoods. Vegetable production and supply chains are particularly vulnerable due to the perishable nature of the products and labor‐intensive production practices. The purpose of this study was to understand the impacts of COVID‐19 on vegetable production in Burkina Faso in terms of both the biophysical aspects such as yields and access to inputs and socioeconomic aspects such as access to labor, markets, and social services. A survey was developed to better understand smallholder farmer experiences regarding the impacts of COVID‐19 on their vegetable production systems and social well‐being. The survey was administered (between August and October 2020) with smallholder farmers ( n = 605) in 13 administrative regions covering all agroecological zones of Burkina Faso. The survey results clearly show impacts of COVID‐19 on vegetable systems, including a reduction in access to inputs, a reduction in yields, a loss of income, reduced access to local and urban markets, reduced access to transportation, and an increase in post‐harvest loss. Market access, distribution, and disruptions were a major shock to the system. Results also showed an increase in women's labor in the household, and for youth, an increase in unemployment, job loss, and concerns of poverty. Finally, food security and social supports were highlighted as major issues for resilience and livelihoods. The results from this survey should be helpful to policymakers and researchers to develop policies and strategies to minimize the negative impacts of this ongoing pandemic on the agri‐food systems and support smallholder farmers to overcome stress caused by COVID‐19. Abstract : Impacts of COVID‐19 experienced by smallholder vegetable farmers in Burkina Faso were collected through surveys. They expressed reduction in access to inputs, reduced yields, loss of income, reduced access to local and urban markets, reduced access to transportation, and increased post‐harvest loss. These impacted lives, livelihoods, and social well‐being of families, especially women and youth.